Deteksi Port Scanning pada Jaringan IoT dengan Pemantauan Web Real-Time - Bilal AlHafidz; Andri Firmansyah; Suherman Suherman (TIN: Terapan Informatika Nusantara, 2026)
Port scanning is a reconnaissance activity that may precede service exploitation on Internet of Things (IoT) devices. This study designs and implements a prototype for detecting TCP port scanning with real-time web monitoring in the local network of PT WIMISEC, Bekasi. The system was developed using a Research and Development approach and Waterfall stages, integrating a Laravel application, a MySQL database, and a Python detection engine. Detection applies a threshold rule based on the number of unique destination ports accessed by one source IP address within a time window. The evaluation covered functional testing, five TCP SYN scans, five TCP Connect scans, three browsing activities, and three normal SSH logins. All 10 scan trials generated alerts (an observed detection rate of 100%), while none of the six normal trials generated an alert (an observed false-positive rate of 0% in the limited sample). The mean latency from detection-engine identification to dashboard alert display was 1.24 seconds. These results demonstrate the prototype's functional feasibility for initial LAN monitoring rather than general accuracy across attack patterns. The evaluation remains limited by its small sample, the absence of mixed-traffic and stress testing, and the lack of tests involving UDP, slow, distributed, and evasive scans.